Metal-free visible-light-induced photoredox-catalyzed intermolecular pyridylation/phosphinoylation of alkenes. Issue 5 (6th January 2021) - Shen, Jiaxuan; Zhang, Yipin; Yu, Yanjiang; Wang, Manman
Abstract : A visible-light-induced and photoredox-catalyzed intermolecular pyridylation/phosphinoylation of alkenes using 4-cyanopyridine and diphenylphosphine oxide under mild metal-free conditions has been reported. Abstract : Reported here is an intermolecular pyridylation/phosphinoylation of alkenes using 4-cyanopyridine and diphenylphosphine oxide under visible-light-induced organic photoredox catalysis. The reaction occurs under mild metal-free conditions, possessing a broad substrate scope. The protocol can be practiced on a gram scale and applied to the modification of natural product-derived and medicinally relevant complex molecules containing a styrene unit. Mechanistic investigations suggest that triethylamine serves as both single-electron transfer (SET) and hydrogen atom transfer (HAT) agents.